Reforming Italy’s long-term care system: the role of barriers to and drivers of the use of services at the local level - Sara Santini; Gianluca Busilacchi; Giovanni Lamura; Federico Sofritti; Antonio Pacifico; Ramona Bongelli; Carmela Guarascio (Frontiers in Public Health)
BackgroundIn Italy, population ageing is causing an unprecedented demand for long-term care (LTC) services, that led to the recent national reform of the LTC system (Law n. 33/2023). Since LTC services are provided by regional authorities, identifying drivers of and barriers to their use by older people and their family caregivers locally is very important to identify the mismatch between national regulation and local demand of these services.MethodsTo this purpose, in 2019-2020, 450 family caregiver (FC)-older care recipient (OCR) dyads from 13 healthcare districts of the Marche region (Central Italy) were surveyed. A Two-step Bayesian Multiclass procedure was used for the analysis. The main drivers of the use of healthcare services are FC’s age and gender (being a man), and OCR’s age and level of disability.ResultsThe main barrier to the use of private services is their cost, while for the public ones is their unavailability. The most common private service is represented by migrant care workers (MCWs), hired privately by the older people’s families.ConclusionFindings suggest that the recent national LTC reform in Italy does not seem to have fully captured the LTC needs of older people, and some policy suggestions are therefore provided in this regard.